Comparative plastomes of Carya species provide new insights into the plastomes evolution and maternal phylogeny of the genus - Xi, Jianwei; Lv, Saibin; Zhang, Weiping; Zhang, Jingbo; Wang, Ketao; Guo, Haobing; Hu, Jie; Yang, Yang; Wang, Jianhua; Xia, Guohua; Fan, Guangyi; Wang, Xinwang; et al. (Frontiers in Plant Science, 2022)
Carya, in the Juglandiodeae subfamily, is to a typical temperate-subtropical forest-tree genus for studying the phylogenetic evolution and intercontinental disjunction between eastern Asia (EA) and North America (NA). Species of the genus have high economic values worldwide for their high-quality wood and the rich healthy factors of their nuts. Although previous efforts based on multiple molecular markers or genome-wide SNPs supported the monophyly of Carya and its two EA and NA major subclades, the maternal phylogeny of Carya still need to be comprehensively evaluated. The variation of Carya plastome has never been thoroughly characterized. Here, we novelly present 19 newly generated plastomes of congeneric Carya species, including the recently rediscovered critically endangered C. poilanei. The overall assessment of plastomes revealed highly conservative in the general structures. Our results indicated that remarkable differences in several plastome features are highly consistent with the EA-NA disjunction and showed the relatively diverse matrilineal sources among EA Carya compared to NA Carya. The maternal phylogenies were conducted with different plastome regions and full-length plastome datasets from 30 plastomes, representing 26 species in six genera of Juglandoideae and Myrica rubra (as root). Six out of seven phylogenetic topologies strongly supported the previously reported relationships among genera of Juglandoideae and the two subclades of EA and NA Carya, but displayed significant incongruencies between species within the EA and NA subclades. The phylogenetic tree generated from full-length plastomes demostrated the optimal topology and revealed significant geographical maternal relationships among Carya species, especially for EA Carya within overlapping distribution areas. The full-length plastome-based phylogenetic topology also strongly supported the taxonomic status of five controversial species as separate species of Carya. Historical and recent introgressive hybridization and plastid captures might contribute to plastome geographic patterns and inconsistencies between topologies built from different datasets, while incomplete lineage sorting could account for the discordance between maternal topology and the previous nuclear genome data-based phylogeny. Our findings highlight full-length plastomes as an ideal tool for exploring maternal relationships among the subclades of Carya, and potentially in other outcrossing perennial woody plants, for resolving plastome phylogenetic relationships.